2020
DOI: 10.1007/s11906-020-01037-1
|View full text |Cite
|
Sign up to set email alerts
|

Megalin: a Novel Determinant of Renin-Angiotensin System Activity in the Kidney?

Abstract: Purpose of Review Megalin is well known for its role in the reabsorption of proteins from the ultrafiltrate. Recent studies suggest that megalin also reabsorbs renin and angiotensinogen. Indeed, without megalin urinary renin and angiotensinogen levels massively increase, and even prorenin becomes detectable in urine. Recent Findings Intriguingly, megalin might also contribute to renal angiotensin production, as evidenced from studies in megalin knockout mice. This review discusses these topics critically, conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 70 publications
1
18
0
Order By: Relevance
“…Urine renin activity may reflect the severity of kidney dysfunction, which emphasizes its importance as a potential marker of maladaptive intrarenal/intratubular RAS activation in patients with type 2 diabetes. The fact that prorenin has been reported as undetectable in the urine [47,48] is consistent with reabsorption of renin by the proximal tubules [49,50] and that renin in urine does not reflect prorenin conversion to renin in the intratubular compartment [50,51]. Unfortunately, most of the studies reporting renin levels in urine utilize commercially available ELISA kits, which rely on prorenin as the standard provided.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Urine renin activity may reflect the severity of kidney dysfunction, which emphasizes its importance as a potential marker of maladaptive intrarenal/intratubular RAS activation in patients with type 2 diabetes. The fact that prorenin has been reported as undetectable in the urine [47,48] is consistent with reabsorption of renin by the proximal tubules [49,50] and that renin in urine does not reflect prorenin conversion to renin in the intratubular compartment [50,51]. Unfortunately, most of the studies reporting renin levels in urine utilize commercially available ELISA kits, which rely on prorenin as the standard provided.…”
Section: Discussionmentioning
confidence: 95%
“…In the present study, the fact that renin activity measured by radioimmunoassay was increased in urine four- and three-fold in men and women with type 2 diabetes, respectively, suggests that active renin was probably generated further down in the distal nephron segments. Recent studies reported that megalin reabsorbs renin in the proximal tubules since megalin knockout mice exhibited excessive urinary excretion of renin [ 49 , 50 ]. Megalin is primarily expressed in the apical brush border of the proximal tubules and contributes to reabsorption of filtered molecules [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The observation that AGT excretion parallels albuminuria in humans but that urinary renin levels relative to albumin excretion are much higher than urinary AGT, suggests that urinary renin levels reflect not only the release of renin by the collecting duct but also renin that is filtered and incompletely reabsorbed by the proximal tubules 138 . Under normal circumstances, the reabsorption of renin and prorenin by the proximal tubule is extensive -potentially close to 100% -suggesting that very little filtered renin and prorenin escapes into the urine 139 . Given this extensive reabsorption of renin and prorenin by the proximal tubule, the finding that prorenin is not detectable in urine 15,116 , despite the fact that renin and prorenin are filtered in larger amounts than albumin, indicates that urinary renin may not reflect the conversion of prorenin to renin in tubular fluid and rather reflects intrarenal renin production 119,139 .…”
Section: Remaining Controversiesmentioning
confidence: 99%
“…Under normal circumstances, the reabsorption of renin and prorenin by the proximal tubule is extensive -potentially close to 100% -suggesting that very little filtered renin and prorenin escapes into the urine 139 . Given this extensive reabsorption of renin and prorenin by the proximal tubule, the finding that prorenin is not detectable in urine 15,116 , despite the fact that renin and prorenin are filtered in larger amounts than albumin, indicates that urinary renin may not reflect the conversion of prorenin to renin in tubular fluid and rather reflects intrarenal renin production 119,139 . One study 13 showed that renin was increased in the urine of patients with type 1 diabetes mellitus and kidney disease, as well in mice with streptozotocin-induced diabetes 13 .…”
Section: Remaining Controversiesmentioning
confidence: 99%
“…The (pro)renin receptor was shown to be involved in the megalin-mediated uptake of renin and other components of the RAS in cell cultures in vitro. [ 9 ]. The present study now provides a good argument that this may happen also in vivo, providing another argument for renin uptake as a source for local RAS activity in the kidney.…”
mentioning
confidence: 99%